Systematic literature review: effects of digital teaching materials on learning achievement - Djono, Djono; Sudiyanto, Sudiyanto; Sukmawati, Fatma; Salimi, Moh (International Journal of Evaluation and Research in Education (IJERE), 2024)
This research aims to examine the effect of digital teaching materials based on their classification on learning achievement at various levels of education. The research design is a systematic literature review (SLR). The stages of conducting a review consist of three major parts: planning, conducting, and reporting. The articles reviewed in this study were drawn from reputable academic databases. The inclusion criteria for this research are as: i) indexed by Scopus; ii) the specified time is 15 years; iii) the research subjects must be students; iv) the minimum number of research participants is 15 people; and v) the article must be a scientific research article. The exclusion criteria in this study are article topics that are outside the field of education. The procedure used to analyze the results of the research obtained using a literature survey. The results showed that the advantages of digital teaching materials, in general, are: i) easy to apply; ii) low-cost; iii) highly flexible; and iv) broad. Each type of digital teaching material has several impacts on learning achievement, including: increasing scientific activities; improving students’ independent learning, self-reflection and metacognitive; reducing learning difficulties; and creating the impression that learning is fun.